Orchid Diversity in Mining Impacted Forest Areas of Odisha: Documentation, Restoration and Conservation Aspect - Sharma, Bhagawati Prashad; Saradar, Binod; Choudhari, Sachin Somalal; Sampatrao, Tambe Satish; Marndi, Sugimani; Kumar, Sanjeet (Indian Forester, 2024)
Orchids are most diverse and widespread groups of flowering plants belong to the family Orchidaceae. They are an important component of any forest ecosystem and have medicinal food and livelihood importance. Climate change and human activity are causing a decline in their population, especially in mining affected areas. Therefore, an attempt has been made to document the orchid diversity in anthropogenic and mining impacted areas of Bonai Forest Division, Odisha, India. This article documented 55 orchids from 27 genera, along with information on their habits, flowering times, and uses.